A Review of the Science of Colorful, Plant-Based Food and Practical Strategies for “Eating the Rainbow” - Deanna M. Minich (Journal of Nutrition and Metabolism)
Over the past decades, thousands of published studies have amassed supporting recommendations to consume fruits and vegetables for physiological and psychological health. Newer research has emerged to suggest that these plant-based foods contain a plethora of not only vitamins and minerals, but perhaps, most importantly, phytonutrients. These phytonutrients have known pleiotropic effects on cellular structure and function, ultimately resulting in the modulation of protein kinases and subsequent epigenetic modification in a manner that leads to improved outcomes. Even though eating fruits and vegetables is a well-known feature of a healthy dietary pattern, population intakes continue to be below federal recommendations. To encourage consumers to include fruits and vegetables into their diet, an “eat by color” approach is proposed in this review. Although each individual food may have numerous effects based on its constituents, the goal of this simplified approach was to identify general patterns of benefits based on the preponderance of scientific data and known mechanisms of food-based constituents. It is suggested that such a consumer-oriented categorization of these plant-based foods may lead to greater recognition of their importance in the daily diet throughout the lifespan. Other adjunctive strategies to heighten awareness of fruits and vegetables are discussed.